2014
DOI: 10.1007/s00418-014-1262-6
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin is necessary for colony growth of human diploid keratinocytes

Abstract: The role of vimentin (Vim) in diploid epithelial cells is not well known. To understand its biological function, we cultured human epidermal keratinocytes under conditions that support migration, proliferation, stratification and terminal differentiation. We identified a keratinocyte subpopulation that shows a p63(+)/α5β1(bright) phenotype and displays Vim intermediate filaments (IFs) besides their keratin IF network. These cells were mainly located at the proliferative/migratory rim of the growing colonies; b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 67 publications
4
17
0
Order By: Relevance
“…We showed that Vim + keratinocytes are mainly located at the periphery of the colony ( Fig. 1A ), and knocking down Vim mRNA, impaired keratinocyte colony growth 13 . Since the growth of a keratinocyte colony depends on the outward migration of the rapidly proliferating cells located in the thin rim of the colony perimeter 18 , and since Vim is involved in cell migration and invasiveness of carcinoma cells 19 , in order to study the role of Vim during diploid epidermal cell migration, we also knocked down Vim mRNA, and determined keratinocyte migration in a specific assay 20 21 , such as the microliter radial monolayer assay (MRMA) described by Berens et al .…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…We showed that Vim + keratinocytes are mainly located at the periphery of the colony ( Fig. 1A ), and knocking down Vim mRNA, impaired keratinocyte colony growth 13 . Since the growth of a keratinocyte colony depends on the outward migration of the rapidly proliferating cells located in the thin rim of the colony perimeter 18 , and since Vim is involved in cell migration and invasiveness of carcinoma cells 19 , in order to study the role of Vim during diploid epidermal cell migration, we also knocked down Vim mRNA, and determined keratinocyte migration in a specific assay 20 21 , such as the microliter radial monolayer assay (MRMA) described by Berens et al .…”
Section: Resultsmentioning
confidence: 86%
“…1A ; ref. 13 . Vim filaments (IFs) were located mainly at the bottom of the cell below the nucleus and at the cell leading edge, which is in close contact with the tissue culture substrate ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High proliferation and migration levels of keratinocytes and low differentiation phenotype are related to rapid and efficient wound healing and thus are key characteristics for epidermal substitutes before grafting. We demonstrated in our study that our process induced high proliferation and expression of vimentin (an epithelial-mesenchymal transition marker linked with high cell motility [44][45][46]) (Fig. 4A).…”
Section: Discussionmentioning
confidence: 61%
“…Vimentin is one of the most abundant mesenchymal protein expressed in mammals [96]. The VIM is evolutionary conserved [20], for this reason, the anti-vimentin clone V9 antibody has been used for the vimentin detection in bovines [97,98].…”
Section: Histopathological Analysismentioning
confidence: 99%